Analyzing Handball Techniques Using A Biomechanical Approach: A Systematic Literature Review - Yopi Hutomo Bhakti; Tandiyo Rahayu; Agus Kristiyanto; Mahalul Azam; Adi S; Hilmy Aliriad (Physical Education Theory and Methodology)
Objectives. The study aimed to examine the use of biomechanical analysis in handball technique.